Anti-HMGCR Specificity of HALIP: A Confirmatory Study - Andrés Baucells; Maria Angeles Martínez; Marcelo Alvarado-Cardenas; Anaís Mariscal; Laura Martinez-Martinez; Cándido Juárez; Albert Selva-O’Callaghan (Journal of Immunology Research)
A distinctive new indirect immunofluorescence pattern in liver tissue has been associated with anti-HMGCR autoantibodies. It is known as HALIP (HMGCR Associated Liver Immunofluorescence Pattern). In this study, we furthered the original studies to demonstrate the association of anti-HMGCR antibodies with the HALIP. Human anti-HMGCR antibodies from patients’ sera were purified and incubated with rat triple tissue (kidney/stomach/liver). A characteristic HALIP was observed. Additionally, a colocalization assay of human anti-HMGCR antibodies with rabbit polyclonal anti-HMGCR antibodies showed colocalization of both immunofluorescence patterns. This study confirms that the HALIP is due to human anti-HMGCR antibodies.